العولمة وتحدياتها التقنية والتكنولوجية على الإدارة دراسة ميدانية لمجموعة من منظمات الأعمال العامة والخاصة في القطر العربي السوري - ميّا, علي; هرمز, نور الدين; ناصر, سماهر محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
العولمة سلاح ذو حدين، فمن ناحية إن ما توفره ظاهرة العولمة يعد فرصاً يجب انتهازها، فهي تحمل بذور التقدم والرقي المتمثلة بمنجزات الثورة التكنولوجية وثورة الاتصالات والمعلومات وظهور الحواسب والانترنيت بهدف خدمة البشرية، ومن جهة ثانية تهدد الشعوب والدول بآثارها السلبية المتمثلة بتهديد الثقافات المحلية وتشويهها عن طريق وسائل الإعلام، ومنافسة السلع الأجنبية والخصخصة وما ينتج عنها من بطالة وفقر، إضافة إلى تفشي الفساد الإداري والمضاربات. وهذا يفرض على الدولة أن تتسلح بالقدرة الكافية للتصدي لكل آثار العولمة والاستفادة من إيجابياتها ما أمكن، وإلا فستكون الدولة مجرد تابع اقتصادي وثقافي وحتى سياسي للغرب، وفي الحالتين يجب أن يكون العالم بأسره مستعداً لقبول أفكار جديدة، ومجرد قبول هذه الأفكار يعني بحد ذاته وضع قيود على الحرية الاقتصادية والاجتماعية و السياسية، لذا قمنا بإعداد هذا البحث محاولين بيان التحديات التي تواجهها الإدارة في ظل العولمة، ثم انتقلنا إلى بيان مجموعة من المفاهيم الإدارية الجديدة والتي تُعدّ وليدة ظاهرة العولمة، علّنا نقدّم فكرة عن خطورة تحديات العولمة ودور الإدارة في مواجهتها باتخاذ الخطوات الإيجابية والصحيحة لا سيّما في دول العالم الثالث. Globalization is a dual weapon. On the one hand, globalization offers a chance to be seized, because it carries the origin of progress and development characterized by the achievements of the technological revolution and telecommunication, the appearance of computers and internet to serve the humanity. On the other hand, it threatens nations and countries with its negative effects characterized by threatening the local cultures and deforming their content by the media, the competition of the foreign goods and privatization, with the accompanying poverty. It moreover leads to the spread of corruption and speculations. This entails that the state should have the ability to face all the effects of globalization, and take advantage of its advantages, otherwise, the state will be just an economic and cultural, and political follower for the west. In both cases the world should be ready to accept new ideas. And just accepting these ideas means putting restrictions on the economic and cultural, and political freedom. Therefore, we carried this research to try to identify the challenges that the administration faces in globalization. We then moved to identify the a group of the administrative concepts that came from globalization, trying to give a brief idea about the dangers of globalization and the role of the administration in facing them by taking the proper and positive steps, especially in the developing countries.